2016
DOI: 10.1371/journal.pone.0167218
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Invasive and Anti-Proliferative Synergism between Docetaxel and a Polynuclear Pd-Spermine Agent

Abstract: The present work is aimed at evaluating the antitumour properties of a Pd(II) dinuclear complex with the biogenic polyamine spermine, by investigating: i) the anti-angiogenic and anti-migration properties of a Pd(II) dinuclear complex with spermine (Pd2Spm); ii) the anti-proliferative activity of Pd2Spm against a triple negative human breast carcinoma (MDA-MB-231); and finally iii) the putative interaction mediated by combination of Pd2Spm with Docetaxel. Anti-invasive (anti-angiogenic and anti-migratory) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Cytotoxicity arises from the selective covalent binding of the metal ions to DNA purine bases at more than one site within the double helix, yielding long-range interstrand adducts. These agents have been synthesised and extensively investigated by the team, to provide a comprehensive set of data on (i) cytotoxicity towards several human cancer cells [6][7][8][9][10], (ii) interactions with DNA and glutathione-mediated resistance pathways [11,12] and (iii) impact on cellular metabolism and intracellular water [12][13][14][15][16]. Vibrational spectroscopy techniques were applied (including inelastic neutron scattering and synchrotron radiation-Fourier transform infrared (FTIR)) coupled to theoretical simulations [4,17,18], as well as synchrotron-based Extended X-ray Absorption Fine Structure (EXAFS) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity arises from the selective covalent binding of the metal ions to DNA purine bases at more than one site within the double helix, yielding long-range interstrand adducts. These agents have been synthesised and extensively investigated by the team, to provide a comprehensive set of data on (i) cytotoxicity towards several human cancer cells [6][7][8][9][10], (ii) interactions with DNA and glutathione-mediated resistance pathways [11,12] and (iii) impact on cellular metabolism and intracellular water [12][13][14][15][16]. Vibrational spectroscopy techniques were applied (including inelastic neutron scattering and synchrotron radiation-Fourier transform infrared (FTIR)) coupled to theoretical simulations [4,17,18], as well as synchrotron-based Extended X-ray Absorption Fine Structure (EXAFS) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy techniques were applied (including inelastic neutron scattering and synchrotron radiation-Fourier transform infrared (FTIR)) coupled to theoretical simulations [4,17,18], as well as synchrotron-based Extended X-ray Absorption Fine Structure (EXAFS) [11]. The dinuclear complex Pd 2 Spm (Spm = spermine, H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH(CH 2 ) 3 NH 2 ), in particular, has yielded quite promising results towards human triple negative (metastatic) breast cancer, coupled to lower toxicity in non-tumorigenic cells [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The dinuclear complexes Pt 2 Spm and Pd 2 Spm have been studied by the authors in the last few years and have been shown to act as promising anticancer agents towards human metastatic breast cancer (Batista de Carvalho et al, 2016a, Batista de Carvalho et al, 2016b, Fiuza et al, 2011, Marques et al, 2002, Silva et al, 2013 and osteosarcoma (Lamego et al, 2017). A multidisciplinary study was presently carried out to attain complementary structural and dynamical information on their interplay with DNA (their main pharmacological target), using QENS measurements, SR-FTIR and SR-EXAFS/XANES.…”
Section: Discussionmentioning
confidence: 99%
“…(Kelland, 2007, Marques, 2013, Wheate, Walker et al, 2010 Among these, polynuclear multifunctional Pt(II) and Pd(II) chelates with flexible biogenic polyamines as bridging ligands have been synthetized by the authors and evaluated as to their effect on several types of human neoplasias, namely the low prognosis, highly metastatic triple negative breast cancer against which a Pd(II) agent (Pd 2 Spm, Spm=spermine, H 2 N(CH 2 ) 3 NH(CH 2 ) 4 NH(CH 2 ) 3 NH 2 ) has yielded particularly promising results. (Fiuza, Holy et al, 2011) A number of studies have been conducted in the last few years on these Pt-and Pd-based complexes, reporting conformational profiles (Batista de Carvalho, Parker et al, 2018, Fiuza, Amado et al, 2015, Marques, Valero et al, 2013 and pharmacokinetic/pharmacodynamic behaviour, (Corduneanu, Chiorcea-Paquim et al, 2010, Marques, Gianolio et al, 2015 and the effect on different human cancers(Batista de Carvalho, Medeiros et al, 2016a, Fiuza, Amado et al, 2006, Fiuza et al, 2011, Marques, Girao et al, 2002, Silva, Andersson et al, 2013, Silva, Fiuza et al, 2014, Soares, Fiuza et al, 2007, Tassoni, Bagni et al, 2010, Teixeira, Seabra et al, 2004, Tummala, Diegelman et al, 2010 including their impact on cellular biochemical profile. (Batista de Carvalho, Pilling et al, 2016b, Lamego, Marques et al, 2017, Marques, Batista de Carvalho et al, 2017 Unconventional pathways of cytotoxicity were disclosed, which are recognized to lead to an improved therapeutic efficiency coupled to a lower toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, such compounds are typically associated to serious systemic toxicity and acquired resistance (mainly via interaction with glutathione and metallothioneins) ( 3 ). Therefore, other metal complexes have been tested, namely containing ruthenium ( 4 , 5 ), titanium ( 6 ), gold ( 7 ), and palladium, Pd ( 8 11 ). Pd(II) compounds have attracted much attention due to the similarity of the metal center to Pt(II) (electronic structure and coordination chemistry) ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%